The intriguing molecular dynamics of Cer[EOS] in rigid skin barrier lipid layers requires improvement of the model - Fandrei, Ferdinand; Havrišák, Tomáš; Opálka, Lukáš; Engberg, Oskar; Smith, Albert A; Pullmannová, Petra; Kučerka, Norbert; Ondrejčeková, Veronika; Demé, Bruno; Nováková, Lucie; Steinhart, Miloš; Vávrová, Kateřina; et al. (Journal of lipid research, 2023)
Omega-O-acyl ceramides such as 32-linoleoyloxydotriacontanoyl sphingosine (Cer[EOS]) are essential components of the lipid skin barrier, which protects our body from excessive water loss and the penetration of unwanted substances. These ceramides drive the lipid assembly to epidermal-specific long periodicity phase (LPP), structurally much different than conventional lipid bilayers. Here, we synthesized Cer[EOS] with selectively deuterated segments of the ultralong N-acyl chain or deuterated or 13C-labeled linoleic acid and studied their molecular behavior in a skin lipid model. Solid-state 2H NMR data revealed surprising molecular dynamics for the ultralong N-acyl chain of Cer[EOS] with increased isotropic motion toward the isotropic ester-bound linoleate. The sphingosine moiety of Cer[EOS] is also highly mobile at skin temperature, in stark contrast to the other LPP components, N-lignoceroyl sphingosine acyl, lignoceric acid, and cholesterol, which are predominantly rigid. The dynamics of the linoleic chain is quantitatively described by distributions of correlation times and using dynamic detector analysis. These NMR results along with neutron diffraction data suggest an LPP structure with alternating fluid (sphingosine chain-rich), rigid (acyl chain-rich), isotropic (linoleate-rich), rigid (acyl-chain rich), and fluid layers (sphingosine chain-rich). Such an arrangement of the skin barrier lipids with rigid layers separated with two different dynamic "fillings" i) agrees well with ultrastructural data, ii) satisfies the need for simultaneous rigidity (to ensure low permeability) and fluidity (to ensure elasticity, accommodate enzymes, or antimicrobial peptides), and iii) offers a straightforward way to remodel the lamellar body lipids into the final lipid barrier.
Keywords: kůže; Linoleic Acid; stratum corneum models; Ceramides; neutron diffraction; sfingosin; kyselina linolová; molecular dynamics; lipid assembly; simulace molekulární dynamiky; Epidermis; long periodicity phase; NMR spectroscopy; Sphingosine; Molecular Dynamics Simulation; ceramidy; lipid chain order; epidermis; Skin